The L. Ron Hubbard Series: Literaly Correspondence Letters & Journals - L. Ron Hubbard (Bridge Publication, Inc., 2012)
If you adventure through life, you have a good chance to be a success on paper. Adventure doesnt mean globe-trotting, exactly, and it doesnt mean great deeds. Adventuring is like art. You have to live it to make it real. (L. Ron Hubbard)